Analysis of Water Scores in Indonesian University to Accelerate the Achievement of SDGs 6 - Valentino Omega Gandi, Valentino Omega Gandi; Sari, Maylia Pramono (Pusat P2M Politeknik Negeri Batam, 2025)
One of the 17 sustainability goals is to have access to sufficient sanitation and clean water. If human health is the main objective, clean water and adequate sanitation are crucial. The enhancement of human life and well-being is influenced by human health, particularly in emerging nations like Indonesia. Thus, the first step in achieving this objective may be education via Indonesian campuses, which is one of the most significant foundations in life. This study attempts to examine the impact of Campus Area as Control Variable (Z) and Water Score or Water Use Score as Variable X on the Total Ratio or contribution of Indonesian campuses to clean water and adequate sanitation. 50 Indonesian campuses that are UI Green Metric members served as samples for this quantitative investigation. The findings of this investigation show that the Total Ratio (Y) is positively impacted by both Campus Area (C) and Water Score (X).